The Use Of Mediation In Industrial Dispute Resolution - Gayo, Sabela (Legalpreneur Journal, 2024)
Administrative legislation and / or economic administrative law that “involves” criminal law in Indonesia is quite a lot. One example is Law No. 20 of 2016 on brands and Geographical Indications involved in the development of industry. Problems of criminal law in the field of administrative law and economic law, especially in the enforcement and protection of intellectual property rights have not shown action in line with the spirit of law formation. One form of violation of the law that is currently growing in Indonesia is duplication of copyright. But so far, efforts to provide legal protection for copyright holders seem inadequate. Even in the process of implementing law enforcement, it is not uncommon for copyright infringement cases to run aground in the middle of the road. Seeing the problems in the enforcement of economic criminal law, especially in the field of intellectual property rights, gave birth to an alternative discourse on the resolution of criminal disputes in the field of intellectual property rights, especially against violations of brand rights. How is the concept of industrial criminal punishment related to brand and geogtaphic indications, and whether mediation is the right choice in resolving industrial disputes.